Menumbuhkan Karakter Keadilan Anak Usia Dini melalui Permainan Tradisional Nusantara (Fokus: Pengembangan Buku Pedoman Pendidikan Karakter) - Rahmawati, Helena Twindi; Nugrahanta, Gregorius Ari (Universitas Cokroaminoto Palopo, 2024)
The prevalence of justice character crisis in children is the main problem in this study. Developing a guidebook of traditional games to foster the character of justice in children aged 7-9 years is the purpose of this research. In this study, the method used was ADDIE-type Research and Development (R&D). Researchers involved ten teachers, ten validators, and eight children aged 7-9 years in the implementation of this study. The results showed that, 1) the product in the form of a justice character guidebook was developed with ADDIE steps, 2) the quality of the research product obtained an average score of 3.71 which fell into the